Foundations of the Rank-Dependent Probability Weighting Function - Matthew D. Rablen (Institute of Labor Economics (IZA), 2019)
The psychological basis for rank-dependent probability weighting, and for an inverse-S probability weighting function (PWF) in particular, has often been questioned. I examine the existence and shape of the PWF in a model allowing for optimism/pessimism over probability distributions and for loss averse/gain loving stochastic reference dependence. I give commonly observed shapes of PWF a psychological interpretation. In particular, I establish a deep connection between two of the most established phenomena in decisionmaking: loss aversion and the inverse-S PWF: the former is a pre- condition for the latter.
Keywords: D81; D01; 330; probability weighting; rank dependent expected utility; loss aversion; reference dependence; optimism; pessimism